If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = 3x + -10 Reorder the terms: -6 + 7x = 3x + -10 Reorder the terms: -6 + 7x = -10 + 3x Solving -6 + 7x = -10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 7x + -3x = -10 + 3x + -3x Combine like terms: 7x + -3x = 4x -6 + 4x = -10 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 4x = -10 + 0 -6 + 4x = -10 Add '6' to each side of the equation. -6 + 6 + 4x = -10 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = -10 + 6 4x = -10 + 6 Combine like terms: -10 + 6 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| 4(x+2.19)=3x | | a-25=-25 | | 200x-0.43=400x+0.03 | | x^2+16*x-438.4=0 | | 4.4x-27=2.9x+6 | | 67-20=2y-4 | | 4x(2+2)+4*6= | | 6y^2+28y-98=0 | | 3p-7=2(4-p) | | 5.6=10x+6.1 | | fx=3(2x-1) | | X/8+4=6 | | 1/4(8x-20)=1/3(15x-6) | | (3-7j)+(9-j)= | | Y-6.8=8 | | 2.5x+9-4.5x=1 | | 6-(6-10*343)= | | 9i/(8-5i) | | 5x-37.6=x | | x^2+16*x+1.2=0 | | 4(y+5)=32 | | 6m=2(5m+10) | | 0.5x+0.6=-1.9 | | [2(4-7)]= | | 3(2g+7)-6g-21=0 | | (x^4-y^4)*(x^4+y^4)=0 | | 2(x-8.8)=4.6 | | -12=4-21 | | 14x+93=261 | | 8=3x+4(-2x) | | 13-2(3x-6)=2(2-4x) | | 7x+5.03=4x+11 |